PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. INDOFOOD FRITOLAY MAKMUR, TBK CABANG MEDAN - Sihombing, Humiras Betty M.; Milala, Rehulina (LPPM Universitas Darma Agung, 2020)
Productivity can be influenced by many factors, including management, ability, discipline, training and work motivation but the most important factors are training and motivation factors. This study aims at determining the effect of training and work motivation partially and simultaneously on employee work productivity at PT. Indofood Fritolay Makmur, Tbk Medan Branch. The population of this study is 115 workers at PT. Indofood Fritolay Makmur, Tbk Medan Branch. To determine the number of samples used Slovin formula, 89 people aredetermined. Data collection techniques in this study are questionnaires, interviews and documentation studies while the data analysis technique used is the classic assumption test, multiple regression, t test, F test and coefficient of determination. The results showed that training and work motivation had a positive and significant effect partially and simultaneously on employee work productivity at PT. Indofood Fritolay Makmur, Tbk Medan Branch. The coefficient of determination (R Square) is 0.643. That is, variations in employee work productivity can be explained by training and work motivation of 64.30%, while the remaining 35.70% is explained by other factors. Thus it is suggested that companies should choose trainer instructors who truly master the training material, and design training materials to suit the needs of all training participants. Chairman of PT. Indofood Fritolay Makmur, Tbk Medan Branch needs to pay attention on its employees by providing financial rewards that are comparable to the work charged to the employees concerned.